Study of influence of structurizing regims on the properties of structural glass-fiber plastics - Karandashov, O.H.; Avramenko, V.L.; Vashchenko, O.V.; Podhornaya, L.F. (Functional Materials, 2018)
Manufacturing of glass-fiber articles under specified strength characteristics, different ratio of layer thickness to inner diameter and without defects and delaminations is investigated. The influence of technological regimes, degree of curing on the physical and mechanical characteristics of glass-fiber articles was studied. In order to estimate the quality of the obtained articles, and to obtain reliable data on the course of the structuring process, methods of extraction, infrared spectroscopy and differential scanning calorimetry were used.